Jurisprudential obligations according to the Inter-American Court in the adaptation of legislation on sexual and institutional violence - Caballero Echevarría, Claudia (2024)
Since its formation, the Inter-American Court has heard a large number of cases of human rights violations, among which it has analyzed investigations into alleged sexual violations and the commission of institutional violence. In this context, there is an urgent need to adapt the domestic legislation of States to address these issues. The objective of this article is to expose the obligations established jurisprudentially by the Inter-American Court on legisla-tion to prevent and eradicate sexual and institutional violence. Thus, based on an analysis of the Court’s historical cases, various types of inter-American standards were identified corresponding to compliance with the obligations assumed by the States parties to the American Convention and the Convention of Belém do Pará. All of these express duties related to the creation, modification and repeal of regulations with the purpose of promoting legal equality and preventing the commission of sexual and institutional violence.